Two Collaborative Projects for Coroplastic Research, IV. The Work of the Academic Years 2016–2017 - Arthur Muller; Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
An international team of 7 researchers has been meeting biannually to collaborate on two projects that are envisaged as aids for coroplastic research. The first is the Handbook for Coroplastic Research (HaCoSt), a tool designed for those new to the field of coroplastic studies. The second project has been nicknamed Winter On-Line. This concerns the creation of a searchable version of Franz Winter, Die Typen der figürlichen Terrakotten, 1903, in wiki format.